Evaluasi Program Prioritas Pembangunan Bidang Pendidikan Provinsi Sumatera Utara - Ade Rahma Sari; Muhammad Arifin Nasution (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
North Sumatra Province-2 priority development programs for 2019-2023, namely increasing and fulfilling access to education. Evaluation of priority development programs in the education sector of North Sumatra Province is aimed at knowing the realization of program achievements, to find out the inhibiting factors in program implementation, to determine the evaluation of development priority programs in the education sector of North Sumatra Province. The research method used is descriptive qualitative. Data collection techniques were carried out by interviews and documentation. The data obtained is then analyzed by examining all the data that has been collected which is supported by the results of interviews with the CIPP theoretical approach by Stufflebeam (1966), namely context, input, process, results. The results of this study have not gone well. This is due to the refocusing of the North Sumatra Province APBD for the construction of new school units in 2020, the limited number of teachers both in quality and quantity, the limited number of scholarships from the North Sumatra Provincial Government, and the lack of synchronization between OPDs in implementing priority programs.